Seasonal investigation of ultrafine-particle organic composition in an eastern Amazonian rainforest - A. E. Thomas; H. S. Glicker; A. B. Guenther; R. Seco; O. Vega Bustillos; J. Tota; R. A. F. Souza; J. N. Smith (Atmospheric Chemistry and Physics)
Reports on the composition of ultrafine particles (<100 nm in diameter) in the Amazon are scarce, due in part to the fact that new-particle formation has rarely been observed near ground level. Ultrafine particles near the surface have nevertheless been observed, leaving open questions regarding the sources and chemistry of their formation and growth, particularly as these vary across seasons. Here, we present measurements of the composition of ultrafine particles collected in the Tapajós National Forest (2.857° S, 54.959° W) during three different seasonal periods: 10–30 September 2016 (SEP), 18 November–23 December 2016 (DEC), and 22 May–21 June 2017 (JUN). Size-selected (5–70 nm) particles were collected daily (for 22 h each day) using an offline sampler. Samples collected during the three time periods were compiled and analyzed using liquid chromatography coupled with Orbitrap high-resolution mass spectrometry. Our findings suggest a sustained influence of isoprene organosulfate chemistry on ultrafine particles from the different periods. We present chemical evidence that indicates that biological-spore fragmentation impacted ultrafine-particle composition during the late wet season (JUN), while chemical markers for biomass burning and secondary chemistry peaked during the dry season (SEP and DEC). Higher oxidation states and degrees of unsaturation were observed for organics in the dry season (SEP and DEC), suggesting greater extents of aerosol aging. Finally, applying a volatility parameterization to the observed compounds suggests that organic sulfur species are likely key drivers of new-particle growth in the region due to their low volatility compared to other species.